Seleksi Bahan Pustaka dalam Pengembangan Koleksi Di UPT Pepustakaan UIN Prof. KH. Saifuddin Zuhri (SAIZU) Purwokerto - Rosydiana, Wildan Novia; Zulaikha, Sri Rohyanti (Jurnal Pustaka Ilmiah, 2022)
The quality of collections in the library is an important parameter in the assessment of a library. As an information provider unit, the library must be able to ensure that the library materials that are held and stored must be in accordance with the needs of the users and the library needs to develop collections for the needs of the users. This study discusses the selection of library materials in the development of collections at the UPT library of UIN Saizu Purwokerto. The purpose of this study was to find out how the selection process for library materials was carried out in developing collections at UPT Saizu UIN library. The research method used is qualitative research by taking four respondents consisting of one head of the library and three librarians in the management of UIN Saizu. The interview technique was carried out in a structured manner using interview guidelines. The observation technique used non-participants by visiting directly to the research location for two weeks. The data validity technique is source triangulation and descriptive research data analysis. The results of this study indicate that the selection of library materials does not run smoothly when carried out by professional librarians who can build collections. Selection of library materials carried out by UPT Saizu UIN library firstly the librarian submits proposals from students who have completed the list of recommendations given by the library, checking library catalogs through OPAC (Online Public Access Catalog) searches, verifying by checking and completing bibliographic data for each title. The tools used by the UIN Saizu library are book scales and publisher catalogs.